Structural Variations in Nucleic Acids Across Different Populations: A Comparative Study - Ziming Sahil (Yayasan Adra Karima Hubbi, 2024)
Structural variations in nucleic acids play a crucial role in genetic diversity and disease susceptibility among different populations. Understanding these variations provides valuable insights into human evolution, genetic predisposition to diseases, and responses to treatments. A comparative study of structural variations across populations is essential to identify population-specific genetic patterns. This study aims to analyze structural variations in nucleic acids across different populations, identify key differences among them, and understand the biological and medical implications of these variations. The ultimate goal is to provide comprehensive data that can be used for further research in population genetics and public health. The study employed a comparative approach using bioinformatics analysis of genomic data from various populations worldwide. Genomic data were obtained from public genomic databases and analyzed to identify structural variations, including deletions, duplications, inversions, and translocations. Next-Generation Sequencing (NGS) techniques were utilized to ensure high accuracy and resolution in identifying structural variations. The results revealed significant differences in structural variations among the populations studied. Certain structural variations were found to be more prevalent in specific populations, indicating natural selection and local adaptation. Additionally, variations associated with genetic diseases showed varying frequencies across populations. This study highlights the importance of structural variations in nucleic acids as a determinant of genetic diversity among different populations. The findings contribute valuable insights into human evolution and have significant implications for health, particularly in developing personalized medical strategies. Further research is needed to explore the impact of these structural variations on biological functions and human health.